The Changing Structure of Chinaâs Pearl River Delta Megacity Region - Song, Junru; Zhao, Min (Journal of Regional and City Planning, 2018)
Based on traditional spatial gravity interaction models, urban quality and the time it takes for people or goods to move between cities are strongly correlated and the extent to which cities are integrated or have the capacity to become integrated into an interconnected urban network changes as travel time between cities changes. This paper analyses Chinaâs Pearl River Delta (PRD) megacity region based on a modified gravity model combined with spatial analysis. It also analyzes economic relations between cities within the PRD megacity region, and compares Chinaâs recent ânew-styleâ urbanization planning in Guangdong Province â the regionâs largest and economically most important province â with planning for Guangdong that pre-dated Chinaâs 2014 National New Style Urbanization Plan. The results show that PRD is now a bi-polar megacity region dominated by Guangzhou and Shenzhen and that four out of six cities the province planned to integrate into the core after 2005 have been integrated, but two have not. In order to build a successful global urban region, PRD needs to continue to improve its core, accelerate the integration of city clusters that can realistically be integrated, continue to study the integration potential of cities with less development potential and pay attention to balanced development of peripheral cities.Keywords. Pearl River Delta, the gravity model, economic spatial connection.Abstrak. Berdasarkan model interaksi gravitasi spasial tradisional, kualitas perkotaan sangat berhubungan dengan waktu tempuh untuk manusia dan barang berpindah dari satu kota ke kota yanglain. Selain itu juga tergantung sejauh mana kota-kota terintegrasi atau memiliki kapasitas untuk terintegrasi ke dalam perubahan jaringan perkotaan yang saling terhubung disebabkan oleh perubahan waktu perjalanan antar kota. Makalah ini menganalisis kawasan mega region Pearl River Delta (PRD) Cina berdasarkan pada model gravitasi yang dimodifikasi yang dikombinasikan dengan analisis spasial. Makalah ini juga menganalisa hubungan ekonomi di antara kota-kota di dalam wilayah megaregion PRD, dan membandingkan perencanaan urbanisasi "gaya baru" di Provinsi Guangdong - provinsi terbesar dan paling penting secara ekonomi di wilayah ini - dengan perencanaan untuk Guangdong yang telah ada sebelum adanya Rencana Urbanisasi Nasional Cina Gaya Baru Tahun 2014. Hasilnya menunjukkan bahwa PRD sekarang menjadi wilayah megaurban bi-polar yang didominasi oleh Guangzhou dan Shenzhen dan bahwa empat dari enam kota yang direncanakan provinsi untuk berintegrasi ke dalam kota inti setelah tahun 2005, namun dua di antaranya belum. Dalam rangka membangun kawasan perkotaan global yang sukses, PRD perlu terus meningkatkan kota intinya, mempercepat integrasi klaster kota yang memang dapat diintegrasikan, terus mengkaji potensi integrasi kota dengan potensi pengembangan yang lebih sedikit dan memberikan perhatian pada keseimbangan pengembangan kota periferal.Kata Kunci. Pearl River Delta, model gravitasi, koneksi spasial ekonomi.